A secure base for mindful dreaming: dispositional and contextually variable attachment security and the experiential quality of dreams. Issue 6 (1st November 2020) - Mikulincer, Mario; Agam, Tali; Shaver, Phillip R.
ABSTRACT: In this study, we examined the utility of attachment theory for explaining individual differences in dream experiences. Seventy-six Israeli undergraduates completed a measure of attachment anxiety and avoidance and participated in a daily diary study for 15 consecutive days. Each evening, they rated their daily sense of attachment security. Each morning, they described in writing any dreams they recalled and rated the extent to which they (a) were aware of their sensations and mental states while dreaming and (b) reflected on their subjective experience during the dream. Two judges made similar ratings for each dream. Dispositional attachment anxiety and avoidance were associated with lower levels of within-dream awareness and reflection across the 15-day period. In addition, attachment security on a given day was associated with higher within-dream awareness and reflection that night. The findings provide new evidence concerning the contribution of attachment orientations to the experiential quality of dreams.